Emerging trends in sustainable treatment and valorisation technologies for plastic wastes in Nigeria: A concise review. Issue 5 (27th April 2021) - Nyakuma, Bemgba B.; Ivase, Tertsegha J.‐P.
Abstract: The article presents an overview of the status, challenges, and prospects of current and emerging trends for the sustainable treatment and valorisation technologies of plastic wastes. The proliferation is ascribed to the growing population, living standards, and use of low cost, unbiodegradable, and chemically resistant plastic wastes in Nigeria. This scenario is exacerbated by the lack of comprehensive strategies for the collection, transport, segregation, and management of plastic wastes. Currently, plastic wastes treatment is accomplished by open‐air burning, dumping, and landfilling. More advanced technologies, such as thermal (incineration, gasification), chemical (catalytic cracking and selective dissolution), and biological (microbial degradation) methods, are also utilized for treatment and valorisation. However, these high‐cost, obsolete, and inefficient technologies result in GHG emissions, toxic fumes, toxins and leachates. Hence, novel technologies for the reuse, recycling, reduction, and valorisation of plastic wastes must emphasize energy, materials, and resource recovery. The article proposes the upcycling of plastic wastes into carbon nanomaterials (carbon microspheres, carbon nanofibers (CNFs), graphene flakes, carbon nanotubes), polymeric composite materials (wood‐polyethylene composites, wood‐fiber‐reinforced plastics), biocrude/bio‐oil, fuels, chemicals, and char through solvent/solvothermal treatment and plasma conversion. Solvent/solvothermal treatment can effectively treat and upcycle plastic wastes along with the removal of toxic, recalcitrant and bio‐accumulative pollutants such as brominated flame retardants and organophosphorus flame retardants. However, the study identified numerous challenges that currently hamper plastic wastes disposal, management, and valorisation. Hence, sustainable and socially friendly approaches for plastic waste management and valorisation are required to address their short‐ and long‐term impacts on human health, safety and the environment in Nigeria.